Extending the Atmospheric River Concept to Aerosols: Climate and Air Quality Impacts. Issue 9 (2nd May 2021) - Chakraborty, Sudip; Guan, Bin; Waliser, Duane E.; da Silva, Arlindo M.; Uluatam, Sophie; Hess, Peter
Abstract: Despite strong impacts that aerosols have on climate and air quality, significant gaps remain in our knowledge concerning their long‐range transport, especially extreme transport events. With this consideration in mind and by leveraging the "atmospheric river" concept, this work develops an objective global algorithm for detecting aerosol atmospheric rivers (AARs), shows a climatology of AARs, elucidates their contributions to major global aerosol transport pathways, and illustrates how AARs can drive extreme cases of poor air quality conditions. Our methodology separately accounts for dust, carbonaceous (accounting for organic and black carbon separately where appropriate), sea salt, and sulfate aerosols. Findings show there are a number of long‐range regional transport pathways where AARs account for a sizable fraction (40% to >100%) of the total transport in relatively few events (20–40 AAR days/year). This study highlights the role of AARs in establishing source‐receptor relationships that can drive regional air‐quality and extremes. Plain Language Summary: Aerosols play an important role in climate and air quality. They can influence climate through their interactions with clouds and precipitation, solar and infrared radiation, and also have adverse impacts on visibility and human health. However, such influences are not confined to their source regions as aerosols can be transported long distances, often across and between continents. This study develops an objective, global atmospheric aerosol rivers (AARs) detection algorithm to identify these narrow and elongated regions of extreme aerosol mass transport. We develop and show AAR climatologies for five major aerosol species, identify their major transport pathways across the globe, and provide a few recent examples of AARs that negatively impacted regional air quality. For the most impactful aerosol species (e.g., sea salt, dust, carbonaceous, sulfate), and for many regions of the globe, we show that a limited number of extreme cases (∼20–40 days per year) of AARs contribute a large fraction (40% to >100%) of the total aerosol transport across a given region. Key Points: Atmospheric aerosol rivers (AARs) account for a sizable fraction of aerosol transport AARs impact the air quality and climate far from their source regions